2022
DOI: 10.2478/auoc-2022-0013
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant potentials and anti-inflammatory properties of methanol extracts of ripe and unripe peels of Ananas comosus (L.) Merr.

Abstract: Studies suggest that extracts from plant materials could play protective roles against various disorders associated with the interplay between oxidative response and inflammatory disorders. The aim of this study was to investigate the potential antioxidant and anti-inflammatory properties, and phytochemical analyses of methanol extract of ripe and unripe peels of Ananas comosus (L.) Merr. The antioxidant properties were investigated through the analyses of ferric ion reducing antioxidant capacities, ascorbic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The results of the study indicated that the extracts exhibited corresponding antioxidant and antiinflammatory properties that can be attributed to characteristic phytochemical constituents. Consequently, the extract may be effective against disorders related to oxidative stress and inflammation (Oso et al, 2022).…”
Section: Issn: 1696-8352mentioning
confidence: 99%
“…The results of the study indicated that the extracts exhibited corresponding antioxidant and antiinflammatory properties that can be attributed to characteristic phytochemical constituents. Consequently, the extract may be effective against disorders related to oxidative stress and inflammation (Oso et al, 2022).…”
Section: Issn: 1696-8352mentioning
confidence: 99%